Typical laryngeal carcinoid tumor with recurrence and lymph node metastasis: a case report and review of the literature - Wang, Qinying (Int J Clin Exp Pathol, 2014)
Typical carcinoid tumor of the larynx is an extremely rare lesion which arises from neuroendocrine cells scanning in the laryngeal mucosa or submucosal glands. Conventionally, it is a well-differentiated neuroendocrine carcinoma, conservative surgery represents the treatment of choice, and the patient usually has a good prognosis with rarely recurrence and metastasis. In this report, we present a case of typical laryngeal carcinoid tumor with recurrence and lymph node metastasis. The patient was a 58-year-old man, complaints of intermittent burning pain in his both ears for 2 years, and for the recent one month the pain turn to continuous accompanied with a mild discomfort in the throat, he had neither hoarseness, dysphagia, nor any otorrhea and hearing loss. The patient was scheduled to undergo a tracheotomy and then a biopsy under supporting laryngoscopy. During the operation, the frozen section diagnosis from the first and the second time both indicated that the biopsy specimens originated from musculo-epithelia, it couldn’t be differed from malignant to benign. So the mass was simply removed under supporting laryngoscopy. The histopathology from paraffin sections revealed typical carcinoid of the larynx and the second procedure consisted of supraglottic laryngectomy with clear margins, the otalgia resolved and the patient had no difficulty with phonation or swallowing. After 1 year follow-up, the patient was found a mass on his right neck with symptom free, B-ultrasonography indicated several enlargement lymph nodes with some merged on both sides of the neck, the patient was scheduled to undergo a “total-laryngectomy with radical neck dissection on the left side and an elective neck dissection on the right side”. The specimens were positive for cytokeratin, chromogranin A and synaptophysin, a final diagnosis of typical carcinoid was made for the recurrence lesion and the metastasis of the lymph nodes. Though the post-operative recovery was uneventful, the prognosis was not good, the patient died six months later. Here, we review the pertinent references on this subject, and discuss the main managements for typical carcinoid tumor of the larynx.